How pragmatic are randomised controlled trials evaluating minimally invasive surgery for oesophageal cancer? A methodological review of trial design using the Pragmatic-Explanatory Continuum Indicator Summary-2 (PRECIS-2) tool - Natalie S Blencowe; Jane Blazeby; Sian Cousins; Katy Chalmers (BMJ Open)
Background Surgical interventions are inherently complex and designing and conducting surgical randomised controlled trials (RCTs) can be challenging. Trial design impacts the applicability of trial results to clinical practice. Given the recent growth in numbers of surgical RCTs, there is a need to better understand the validity and applicability of trials in this field.Objectives To examine the applicability and validity of RCTs comparing minimally invasive and open surgery for oesophageal cancer and to delineate areas for future research.Eligibility criteria RCTs comparing open with minimal invasive oesophagectomy, published January 2012–June 2023. Abstracts, pilot and feasibility studies, and systematic reviews were excluded.Sources of evidence Three sequential searches of Ovid MEDLINE, Embase and CENTRAL electronic databases and clinical trials registry databases.Charting methods Two independent reviewers screened the articles and used appropriate, validated tools (Pragmatic-Explanatory Continuum Indicator Summary-2 (PRECIS-2) and Risk of Bias 2) to assess study quality. Trials were considered pragmatic if they were conducted in multiple centres and had a mean score of four or above on the PRECIS-2.Results Nine RCTs were identified. One was judged to be pragmatic. The remaining eight were limited by narrow eligibility criteria, being single-centred or having strict intervention protocols. Two studies were low risk of bias, of which one was pragmatic, and three high, due to unblinded outcome assessment. The remaining four studies were of ‘some concern’ due to poor reporting.Conclusions Only one trial identified in this review was considered pragmatic. More lenient criteria, as used in other reviews, may increase the proportion. There is a need for clearer guidance on the cut-off values that define a trial as pragmatic. It is recommended that the intended purpose of the trial, whether explanatory or pragmatic, receives more attention during surgical trial study design and conduct.